Electrostatic Interaction of Bilayer Macroparticles - Filippov, A. V. (Journal of experimental and theoretical physics, 2023)
The effect of a dielectric film on the surface of conducting dust particles on their electrostatic interaction is investigated. Special attention is paid to the case when the radius of one of particles is much larger than the radius of the other particle and to a nonuniform distribution of the surface charge with variants of equilibrium free charge distribution on each of the macroparticles over the entire surface and over the left and/or right hemispheres. The technique for calculating of slowly converging series is worked out using the hypergeometric Gauss functions and by introducing new functions for which recurrent relations and numerical calculation technique were determined.